THE ROLE AND IMPORTANCE OF MOTIVATION OF HRM - Arnel Kalušić; Munir Talović; Šemso Ormanović (Sport Scientific And Practical Aspects, 2025)
One way of managing human resources is through motivation. The theme of motivation and factors that motivate workers to increase the effectiveness and effectiveness of work is a complex topic. Motivation implies the will of the individual to make an effort in the activities he meets to meet the needs. Productivity, commitment to the organization is directly related to the motivation of human resources. Motivation is crucial for standard business, for encouraging creativity and innovation, for professional development of employees and their retention in the company. The methodology of work is to write a transparent article according to the traditional principle. By systematically searching for relevant articles related to management issues in order to achieve efficiency, it will create comprehensibility in the knowledge of the basic principles of human resources management. The aim of the paper is to point out the importance of material motivation for the successful operation of the organization. Finding the best way to successfully implement and encourage efficiency and effectiveness in a particular organization, or increasing the efficiency and productivity of its employees is leading idea of each leader. By reviewing the Google Scolar databases, DOAJ, researchgate, Scribd, 12 articles were valid for writing the topic. Additionally, 4 master’s theses from the BiH region and one participant are included. The results suggest that the most qualitative form of human capital management in order to achieve work efficiency and effectiveness is to motivate material and non-material assets. Other forms suggest mainly old forms of autocratic guidance that do not have adequate efficacy and work productivity. Most leaders should manage human resources as a leader who motivates their workers